AN INVESTIGATION INTO THE CORRELATION BETWEEN PERCEPTUAL LEARNING STYLE PREFERENCE AND LISTENING COMPREHENSION - Ria Karina Putri; Ismail Petrus; Rita Hayati (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2018)
Abstract: The objective of this study is to find out whether or not there is a significant correlation between perceptual learning style preference and listening comprehension of students of English Education Study Program, Sriwijaya University. The population of this study was the first, third, fifth and seventh semester students of English Education Study Program of Sriwijaya University in academic year 2017/2018. However, only the fifth and seventh semester students were taken as the sample by using purposive sampling. A descriptive method was used in this study. Specifically, this study was a correlation study. The data were obtained by means of questionnaire and listening comprehension test. The questionnaire showed that the students mostly were in medium level of learning style level and most of them had four major learning styles. Meanwhile, the listening test showed that most students were in Average category. The data obtained were analyzed by using correlation analysis and the result showed that there was no correlation between perceptual learning style preference and listening comprehension of students of English Education Study Program, Sriwijaya University since the value of r-obtained (-.156) was lower than the critical value of r-table (0.197) at the significance level 0.05. Keywords: perceptual learning style preference, listening comprehension